Controlling Poinsettia (Euphorbia pulcherrima Will.) Height with Growth Retardant Application in West Java, Indonesia - Sukma, Dewi; Megawati, Gina (Department of Agronomy and Horticulture, IPB University, 2016)
A study was conducted to evaluate the effects of the growth retardant Cycocel application in the growth and development of poinsettia (Euphorbia pulcherrima) ‘Freedom Red’. Cycocel was applied by spraying plant shoots at the concentrations of 1000, 1500, 2000, 2500 ppm. The increase in cycocel concentrations reduced plant height, leaf size, internodal length, plant spread and the number of flowering plants. All cycocel concentrations resulted in an ideal potted plant height. The optimum spray concentration of Cycocel used to obtain compact and uniformly flowering plants under tropical West Java environment was 1000 ppm.